An ecosocial work model for social work education in Africa - Tadesse, Michael Emru; Obeng, James Kutu (National Association of Social Workers, 2023)
There is a growing call for social work to contribute to the international movement towards sustainability to address the interconnected multiple ecological, social, and economic crises created by the global capitalist hegemony. This call is important for African social work given vulnerable people in Africa are primary victims of unsustainability. In this paper, we propose a model of an ecosocial work course for African undergraduate social work education. This proposal is based on our earlier review of the Bachelor of Social Work curricula of 12 universities in four African countries to determine the extent to which ecosocial contents were addressed. Our review indicated the absence of an ecosocial approach in the curricula. To fill this gap, we then designed a model of an ecosocial work course based on our international experience in social work, our ongoing studies on sustainability, and relevant literature regarding Africa. We hope this model will be adopted by social work programmes in different African universities and used to shape social work students who will deal with the interconnected multiple crises in their practice. We also hope that this proposal will help African social work play a crucial role in the sustainable development of the continent.
Keywords: Africa; Bachelor of Social Work; social work curriculum; ecosocial work; environment; social work; sustainability